Double-Stranded RNA Targeting Dicer-Like Genes Compromises the Pathogenicity of Plasmopara viticola on Grapevine - Haile, Zeraye Mehari; Gebremichael, Daniel Endale; Capriotti, Luca; Molesini, Barbara; Negrini, Francesca; Collina, Marina; Sabbadini, Silvia; Mezzetti, Bruno; Baraldi, Elena (Frontiers in Plant Science, 2021)
Downy mildew caused by Plasmopara viticola, is one of the most devastating diseases of grapevine, attacking all the green parts of the plant. The damage is severe when the infection is left uncontrolled at flowering stage. P. viticola management consumes a significant amount of the classical pesticides applied in vineyards, requiring efficient and environmentally safe disease management option. Spray‐induced gene silencing (SIGS), through the application of exogenous double‐stranded RNA (dsRNA), has shown promising results for the management of diseases in crops. Here, we developed and tested the potential of dsRNA targeting P. viticola Dicer-like (DCLs) genes for SIGS-based crop protection strategy. The exogenous application of PvDCL1/2 dsRNA, a chimera of PvDCL1 and PvDCL2, highly affected the virulence of P. viticola. The reduced expression level of PvDCL1 and PvDCL2 in leaves treated with PvDCL1/2 dsRNA and infected with the oomycete was an indication of the active RNA interference mechanism of the pathogen was going on to compromise its virulence. Besides the protective property, the PvDCL1/2dsRNAalso exhibited curative role by reducing the disease progress rate of already established infection. Our data provide a promising future for PvDCL1/2 dsRNA as a new generation of RNA-based resistant plants or RNA-based agrochemical for the management of downy mildew disease in grapevine.